The Systemic Inflammation Score is Associated with the Survival of Patients with Prostate Cancer - Xie J; Xiao X; Dong Z; Wang Q (Dove Medical Press, 2023)
Jie Xie,* Xu Xiao,* Zhenjia Dong, Qiangdong Wang Department of Urology, the Fifth People's Hospital of Huai'an, Huai'an City, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiangdong Wang, Email fhhywm@163.comBackground: The systemic inflammation score (SIS) based on the albumin (Alb) level and lymphocyte-to-monocyte ratio (LMR), has been associated with survival in some cancers. However, its prognostic role in prostate cancer (PCa) remains unclear.Methods: The associations between the SIS and the clinicopathological features of PCa were evaluated. The correlations between the SIS and overall survival (OS) and progression-free survival (PFS) were assessed using Kaplan-Meier analysis and the Log rank test. Univariate and multivariate Cox analyses were conducted to determine the prognostic factors for PCa. Hazard ratios and 95% confidence intervals were calculated.Results: A total of 253 patients with PCa were included in this study. The Kaplan-Meier analysis and Log rank test suggested that patients with a higher Alb level, higher LMR, or a lower SIS had better 5-year OS and PFS compared with patients with a lower Alb level or lower LMR or higher SIS. Univariate and multivariate Cox analyses showed that drinking, prostate-specific antigen level > 100 ng/mL, and neutrophil-to-lymphocyte ratio > 2.09 were significant prognostic factors for OS and PFS in patients with PCa. Nomograms for 5-year OS and PFS were established with concordance index values of 0.888 and 0.824, respectively. The calibration curve was consistent between the actual observations and the prediction nomogram for OS and PFS probability at 5 years.Conclusion: A high SIS is associated with unfavorable survival in patients with PCa. The SIS serves as a novel independent prognostic factor for OS in patients with PCa.Keywords: systemic inflammation score, prostate cancer, progression-free survival, overall survival